Evaluation of two population screening programmes for BRCA1/2 founder mutations in the Australian Jewish community: a protocol paper. Issue 6 (25th June 2021) - Cousens, Nicole E; Tiller, Jane; Meiser, Bettina; Barlow-Stewart, Kristine; Rowley, Simone; Ko, Yi-An; Mahale, Sakshi; Campbell, Ian G; Kaur, Rajneesh; Bankier, Agnes; Burnett, Leslie; Jacobs, Chris; et al.
Abstract : Introduction: People of Ashkenazi Jewish (AJ) ancestry are more likely than unselected populations to have a BRCA1/2 pathogenic variant, which cause a significantly increased risk of breast, ovarian and prostate cancer. Three specific BRCA1/2 pathogenic variants, referred to as BRCA -Jewish founder mutations (B-JFM), account for >90% of BRCA1/2 pathogenic variants in people of AJ ancestry. Current practice of identifying eligible individuals for BRCA testing based on personal and/or family history has been shown to miss at least 50% of people who have one of these variants. Here we describe the protocol of the JeneScreen study—a study established to develop and evaluate two different population-based B-JFM screening programmes, offered to people of Jewish ancestry in Sydney and Melbourne, Australia. Methods and analysis: To rmeasure the acceptability of population-based B-JFM screening in Australia, two screening programmes using different methodologies have been developed. The Sydney JeneScreen programme provides information and obtains informed consent by way of an online tool. The Melbourne JeneScreen programme does this by way of community sessions attended in person. Participants complete questionnaires to measure clinical and psychosocial outcomes at baseline, and for those who have testing, 2 weeks postresult. Participants who decline testing are sent a questionnaire regarding reasons for declining. Participants with a B-JFM are sent questionnaires 12-month and 24-month post-testing. The questionnaires incorporate validated scales, which measure anxiety, decisional conflict and regret, and test-related distress and positive experiences, and other items specifically developed or adapted for the study. These measures will be assessed for each programme and the two population-based B-JFM screening methods will be compared. Ethics and dissemination: Institutional Human Research Ethics Committee approval was obtained from the South Eastern Area Health Service Human Research Ethics Committee: HREC Ref 16/125.Following the analysis of the study results, the findings will be disseminated widely through conferences and publications, and directly to participants in writing.